STUDI GERUSAN DI HILIR BENDUNG KOLAM OLAK TIPE VLUGHTER DENGAN PERLINDUNGAN GROUNDSILL - Adi Daning Pangestu; Sri Amini Yuni Astuti (TEKNISIA, 2018)
Weir is a river building designed to meet the needs of irrigation. River containment will result in considerable elevation differences between upstream and downstream weirs and result in hydraulic jumps. Hydraulic jumps that occur downstream of the weir will cause scouring downstream of the dam to damage the stability of the weir. So that in the planning of weir there is energy damper of stilling basin. Given the complexity and importance of the problems occurring downstream, the study of scouring downstream from weirs due to the influence of flow to river discharge needs to be given special attention, so that later it can be seen the scouring pattern and the scour depth that occurs. A study on scouring downstream of weirs was conducted in a laboratory with a weir model using a stilling basin vlughter type pond that flowed with three variations of discharge, testing each variation of the flow for 60 minutes. Then tested by giving  protection at downstream weir using groundsill with distance Lmax and ½ Lmax. The experimental results show the greater the flow discharge the greater the scour depth and the flow characteristic values such as the Froude and Reynold numbers. The sediment transport balance was obtained during observation of scour depth at 50 minutes. With the protection of groundsill provide reduction of scour depth by 13.1579% at the groundsill of Lmax distance and 9.2105% at groundill distance of  ½ Lmax.